1991
DOI: 10.1073/pnas.88.17.7491
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, molecular characterization, and chromosomal assignment of a gene encoding a second D1 dopamine receptor subtype: differential expression pattern in rat brain compared with the D1A receptor.

Abstract: Multiple DI dopaminergic receptor subtypes have been postulated on the basis of pharmacological, biochemical, and genetic studies. We describe the isolation and characterization of a rat gene encoding a dopamine receptor that is structurally and functionally similar to the D1 dopamine receptor. The coding region, which is intronless, encodes a protein of 475 amino acids (Mr 52,834) with structural features that are consistent with receptors coupled to guanine nucleotide-binding regulatory proteins. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
174
1
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(197 citation statements)
references
References 32 publications
19
174
1
3
Order By: Relevance
“…It has been reported that the substituted mutation of a hydrophobic motif, or the truncated mutation of C-terminus would disturb the cell surface targeting of D1R [22,23] . The two D1-like receptor subtypes, D1R and D5R, exhibit more diversity in their C-termini amino acid sequence than that in transmembrane segments [4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the substituted mutation of a hydrophobic motif, or the truncated mutation of C-terminus would disturb the cell surface targeting of D1R [22,23] . The two D1-like receptor subtypes, D1R and D5R, exhibit more diversity in their C-termini amino acid sequence than that in transmembrane segments [4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms have been attributed to the different receptor subtypes, their differential affinities to agonist and their differential cellular or subcellular distributions [1,5,6,[31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Received April 17, 1998; revised August 27, 1998; accepted September 21, 1998. (Zhou et al 1990;Monsma et al 1990;Sunahara et al 1990;Dearry et al 1990) and D 1B (Tiberi et al 1991) or D 5 (Sunahara et al 1991], both of these linked functionally to stimulation of cAMP synthesis, and preferentially recognizing 1-phenyl-tetrahydrobenzazepines (e.g., SCH23390). The D 2 -like receptors come from at least three genes and include multiple splice variants.…”
mentioning
confidence: 99%